Caracterización histopatológica de órganos del tracto gastrointestinal en ranas de la especie Gastrotheca spp. Afectadas por el síndrome de edema dentro del centro balsa de los sapos - Cando Chicaiza, Paola Carolina (2017)
A frequent problem in populations in captivity worldwide is the presentation of different disorders that put their conservation status at risk. The institution "Balsa de los Sapos", belonging to the "Pontificia Universidad Católica del Ecuador", is not excluded from this problem, where the Edema Syndrome is present and affect amphibians of the genus Gastrotheca spp., which are marsupial frogs endemic species currently on the IUCN Red List of Endangered Species as endangered Species (IUCN, 2017). The study had a total of 10 individuals of the species Gastrotheca litonedis (n equal 3), Gastrotheca pseustes (n equal 3) and Gastrotheca riobambae (n equal 4) affected by the Syndrome. The main objective of the investigation was the histopathological characterization of organs of the gastrointestinal tract in which the tongue, esophagus, stomach, small intestine, large intestine, and pancreas were included. As a second point, we proceeded to identify their respective primary and secondary lesions. The histopathological reading was performed with histological plates previously processed from all the previously mentioned organs in the Laboratory of Histopathology of the "Universidad de Las Américas". Primary lesions determined the main diagnoses and were: enteritis 60 percent (6/10), glossitis 10 percent (1/10) and pancreatitis 60 percent (6/10). Secondary lesions were characterized as mild, focal, vascular, and inflammatory processes and were found in all organs. A relevant finding was the existence of parasites such as Strongyloides sp, Oxyuris sp, ciliated protozoan and Protoopalina sp. that have not been reported histopathologically on individuals of the Hemiphractidae family in Ecuador. With the final analysis of these organs it expands and complements the knowledge regarding this pathology, in addition it is motivated to develop new studies with a greater depth.